2007
DOI: 10.1039/b713167d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the aminolysis of aryl ethyl chloro and chlorothio phosphates with anilines

Abstract: The reactions of ethyl Y-phenyl chloro (1) and chlorothio (2) phosphates with X-anilines in acetonitrile at 55.0 degrees C are studied kinetically and theoretically. Kinetic results yield the primary kinetic isotope effects (k(H)/k(D) = 1.07-1.80 and 1.06-1.27 for 1 and 2, respectively) with deuterated aniline (XC(6)H(4)ND(2)) nucleophiles, and the cross-interaction constants rho(XY) = -0.60 and -0.28 for and , respectively. A concerted mechanism involving a partial frontside attack through a hydrogen-bonded, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Y-aryl ethyl chlorophosphates were prepared as previously described. 20 The physical constants of Y = (4-MeO, 4-Me, H, 3-MeO) were reported earlier 20 and those of ethyl 3-methylphenyl chlorophosphate were as follows (supporting information): Kinetic Measurements. The second-order rate constants and selectivity parameters were obtained as reported earlier.…”
Section: Methodsmentioning
confidence: 91%
“…Y-aryl ethyl chlorophosphates were prepared as previously described. 20 The physical constants of Y = (4-MeO, 4-Me, H, 3-MeO) were reported earlier 20 and those of ethyl 3-methylphenyl chlorophosphate were as follows (supporting information): Kinetic Measurements. The second-order rate constants and selectivity parameters were obtained as reported earlier.…”
Section: Methodsmentioning
confidence: 91%
“…The anilinolyses of tetracoordinate phosphorus with the Cl -leaving group have been studied extensively in this laboratory, and the data obtained for primary normal DKIEs involving deuterated anilines were rationalized by TSf-type, in which hydrogen bonding of an amine hydrogen atom occurs to the departing chloride. [32][33][34][35][36][37][38] The authors also suggested TSf-type in which hydrogen bonding of an amine hydrogen atom occurs to the departing phenoxy oxygen atom for the anilinolyses of aryl dimethyl, methyl and diphenyl phosphinates. Table 5 lists the activation parameters, enthalpies and entropies of activation, for the reactions of Y-aryl ethyl isothiocyanophosphates with unsubstituted aniline.…”
Section: -7mentioning
confidence: 99%
“…2,5,[6][7][8] The anilinolyses 5,6,7a-j and pyridinolyses 2,8a,c,e,f,g of R 1 R 2 P(=O or S)Cl-type substrates are extensively studied in MeCN. A backside and frontside nucleophilic attack were discussed on the basis of the deuterium kinetic isotope effects (DKIEs; k H /k D ), selectivity parameters (ρ X , ρ Y , β X , and ρ XY ) and free energy correlations (linear, biphasic concave upwards/downwards) for variation of substituent X and Y in the nucleophile and substrate, respectively.…”
Section: 7dmentioning
confidence: 99%
“…2,[5][6][7]15 The real primary normal DKIE due to the hydrogen bond between the hydrogen of the N-H(D) moiety and the leaving group should be greater than the observed value, since the secondary inverse DKIE (k H /k D < 1) because of the steric hindrance that increases the out-of-plane bending vibrational The reaction mechanism of the anilinolyses of R 1 R 2 P (=O or S)Cl in MeCN in Table 1 were rationalized mainly based on the cross-interaction constants (CICs), 16 selectivity parameters (ρ X and β X ), and DKIEs. In O(PhO,PhO) and S(PhO,PhO), a concerted S N 2 mechanism was proposed on the basis of a negative ρ XY value (ρ XY = -1.31 and -0.22, respectively).…”
Section: 7dmentioning
confidence: 99%